A Novel Data Association Method for Frequency Based MIMO Systems - Kalkan, Yilmaz (Společnost pro radioelektronické inženýrství, 2016)
Whenever more than one target exist, the most important problem is associating the received signals to the correct targets. This problem appears for all multiple target applications such as multiple target tracking and it is known as "Data Association". For frequency-based systems, Multiple-Input Multiple-Output (MIMO) configuration together with the frequency diversity of the system enable us to determine the number of moving targets by using the Doppler frequencies. These frequencies include all relevant information about the location, velocity and direction of the targets and hence, they can be used efficiently to estimate the other unknown target parameters.
Keywords: Data association; MIMO radar; frequency-only; Doppler frequency